The main trends in the sociodynamics of culture in the transforming discourse of globalization - Radevich, Ekaterina V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article discusses the main trends in the socio-dynamics of culture in the post-modern era, which are determined by the processes of globalization. The analysis of this phenomenon also undergoes certain transformations in modern social and philosophical discourse – from its pronounced assessments in terms of homogenization, standardization and convergence to trends of particularism, separatism and clearly articulated divergence. Analysis of these processes makes it possible to identify the main features of the sociodynamics of modern society, to identify the main vectors of cultural development of world civilization, to identify the positive and negative aspects of globalization at the present stage of development of society.
Keywords: culture; globalization; convergence; divergence; sociodynamics of culture; identification